The linkages between FDI and domestic investment: Unravelling the developmental impact of foreign investment - Leonce Ndikumana; Sher Verick (University of Massachusetts, Department of Economics, 2007)
Despite the recent increase in foreign direct investment (FDI) to African countries, these resources have not had a meaningful impact on economic development because of limited effects on domestic factor markets, especially domestic investment and employment. In this context, this study analyses the two-way linkages between FDI and domestic investment in Sub-Saharan Africa. The results suggest that firstly, FDI crowds in domestic investment, and secondly, countries will gain much from measures aimed at improving the domestic investment climate. Moreover, there are alternatives to resource endowments as a means of attracting foreign investment to nonresource rich countries.
Keywords: E22; F21; F23; 330; FDI; private investment; public investment; Africa; Direktinvestition; Investition; Beschäftigungseffekt; Infrastrukturinvestition; Standortfaktor; Entwicklung; Afrika südlich der Sahara